PENGARUH SEKTOR PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN LOMBOK BARAT - Risman Khikmallah, Lalu Muhammad (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to confirm the effect of the tourism sector to absorb labor in West Lombok District. This study uses a quantitive approach. The data used are primary data and secondary data in the form of panel data. The method used to collect data in this reaserch is by distributing quetionnaries and conducting interviews (primary data), and data from the Department of Tourism in West Lombok District. The independent variables in this study is the Number of Businesses Tourism (X1), Number of Destinations (X2), Number of Tourist Arrivals (X3), and The Wages Averages (X4), as well as the dependent variable, namely Total Employment (Y) is absorbed by sector tourism. The analysis technique used is multiple linear regression. Based on the result of this reaserch is that the regression equation is found determinant coefficient (R2) was 0.628293, which means the variables x1, x2, x3, and x4 affects the amount of employment in West Lombok district and the rest influenced by others variables outside the research. Meanwhile, if viewed from the influence of each independent variable on theÂ  dependent variable it can be seen that the variables x1, x2, and x3 significant effect on employment in the tourism sector, while the variable x4 no significant effect.Keywords : Number of Businesses Tourism, Number of Destinations, Number of Tourist Arrivals, The Wages Averages, and the Number of Employment.